Mocavita: The Healthy Noodles As A Functional Food Inovation For Stunting Prevention - Musabbih Najil Hakim Rachmat; Chiquita Kamila; Hilda Wulan Cahyani; Rucika Galvani Putri; Musa’adah Musa’adah; Ateng Supriatna (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Stunting is one of the global scale problems in the health sector. Stunting is the condition of impaired growth and development of the children. Stunting is related to the increases in morbidity, death, and decreased or inhibited physical, motoric or functional body and mental growth especially in children. Based on Riset Kesehatan Dasar (Riskedas), Indonesia is ranked 2nd highest stunting cases in Southeast Asia and the 5th highest in the world in 2018. One of the major causes of stunting is nutritional fulfillment or nutrient intake, absorption and utilization of mother or children. Therefore, it is needed to make functional food innovation that can solve this problem. This study aim is to make a functional food innovation based on healthy noodles for children also mother to prevent stunting. This study was carried out by making healthy noodles namely Mocavita. Mocavita is made from kenikir, pumpkin, mocaf flour and mung beans flour as ingredients which then creates into 3 formulas (F1, F2 and F3). Organoleptic test was conducted to know which one of the formulas that is most liked by people. It is found that Mocavita made from Formula 1 is the best and the most liked by 30 panelists.